Emerging trends in a period-radius distribution of close-in planets - Beauge, Cristian (2013)
We analyze the distribution of extrasolar planets (both confirmed and Kepler candidates) according to their orbital periods P and planetary radii R. Among confirmed planets, we find compelling evidence for a paucity of bodies with 3 R⊕ < R < 10 R⊕, where R ⊕ is Earth's radius and P < 2-3 days. We have christened this region a sub-Jovian Pampas. The same trend is detected in multiplanet Kepler candidates. Although approximately 16 Kepler single-planet candidates inhabit this Pampas, at least 7 are probable false positives (FPs). This last number could be significantly higher if the ratio of FPs is higher than 10%, as suggested by recent studies. In a second part of the paper we analyze the distribution of planets in the (P, R) plane according to stellar metallicities. We find two interesting trends: (1) a lack of small planets (R < 4 R ⊕) with orbital periods P < 5 days in metal-poor stars and (2) a paucity of sub-Jovian planets (4 R⊕ < R < 8 R ⊕) with P < 100 days, also around metal-poor stars. Although all these trends are preliminary, they appear statistically significant and deserve further scrutiny. If confirmed, they could represent important constraints on theories of planetary formation and dynamical evolution.